Interacciones medicamentosas potenciales en prescripciones médicas del servicio de geriatría del Hospital Nacional Almanzor Aguinaga Asenjo durante marzo-junio del 2007” - Portilla Palomino, Esther (2008)
The purpose of this study was to identify potential drug interactions that occur in medical prescriptions of service geriatrics of the National Hospital Almanzor Aguinaga Asenjo during March to June 2007. It is a descriptive study, retrospective and cross where they reviewed a total of 177 pharmacological profiles, which met the inclusion and exclusion criteria, which were subject to assessment to identify potential drug interactions that occur in the prescriptions using the bibliography – analytical method. Of the total pharmacological profiles, 68.93% had potential drug interactions, the 59.62% of them were kind of pharmacokinetic and 40.38%, pharmacodynamic. The most frequent drug interactions we Captopril - Furosemide (16.86%), Phenytoin - Ranitidine (0.86%). The drug interactions with potential clinical significance 1, 2 and 3 accounted for 67.31% of total drug interactions found. The drugs most often present in potential drug interactions were: Furosemide, Captopril, Phenytoin Amikacin, ferrous sulphate.